Using Distribution Alliance to Signal the Seller's Service Quality in Online Retailing Platforms. (17th September 2021) - Yan, Yufei; Ye, Zuoliang; Gong, Xiaoxiao
Abstract : Signal plays a significant role in the online retailing market, especially where the service quality of sellers is unobservable. In the current study, a game-theoretical model was formulated to help examine whether the new delivery service called distribution alliance in the electronic market can serve as a superior signal in revealing online seller's service quality. Our results showed that the certification accuracy and the application fee are closely related to the signaling effect of the distribution alliance. Specifically, we found a concrete analytical boundary where a certain high level of certification accuracy is required to guarantee the existence of market equilibrium, and a corresponding application fee can convoy the signal's effectiveness. In addition, the potential extensions and limitations of this research were also discussed.